2015
DOI: 10.1002/ajmg.a.37338
|View full text |Cite
|
Sign up to set email alerts
|

NBAS mutations cause a multisystem disorder involving bone, connective tissue, liver, immune system, and retina

Abstract: We report two unrelated patients with a multisystem disease involving liver, eye, immune system, connective tissue, and bone, caused by biallelic mutations in the neuroblastoma amplified sequence (NBAS) gene. Both presented as infants with recurrent episodes triggered by fever with vomiting, dehydration, and elevated transaminases. They had frequent infections, hypogammaglobulinemia, reduced natural killer cells, and the Pelger-Huët anomaly of their granulocytes. Their facial features were similar with a point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
70
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 15 publications
(32 reference statements)
9
70
1
Order By: Relevance
“…With this report, 23 NBAS -disease children with recurrent liver crises are described: 14 from European countries [12, 14, 19], 3 from the United States [12, 14], 3 from Lebanon (siblings; parental consanguinity known) [13], and our 3 Han Chinese. These patients’ phenotypes range from isolated RALF to RALF in association with multisystemic disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With this report, 23 NBAS -disease children with recurrent liver crises are described: 14 from European countries [12, 14, 19], 3 from the United States [12, 14], 3 from Lebanon (siblings; parental consanguinity known) [13], and our 3 Han Chinese. These patients’ phenotypes range from isolated RALF to RALF in association with multisystemic disease.…”
Section: Discussionmentioning
confidence: 99%
“…NBAS was previously linked to SOPH (short stature, optic nerve atrophy, and Pelger–Huët anomaly of granulocytes; MIM614800) syndrome in an isolated Russian Yakut population, but without liver failure [11]. Further observations expanded the phenotype spectrum of NBAS disease to involve brain, connective tissues other than bone, and the immune system as well [1215]. …”
Section: Introductionmentioning
confidence: 99%
“…This mode of action is inextricably linked to the formation of rings of TANGO1 at ERES (Liu et al 2017; Raote et al 2017). NBAS mutations in humans cause multisystem disorders (Segarra et al 2015) that do include defects in bone formation (Balasubramanian et al 2017) and can therefore be linked to impaired procollagen transport.…”
Section: Efficient Assembly Of the Copii Coat As A Prerequisite For Pmentioning
confidence: 99%
“…So far, 47 different pathogenic NBAS variants have been reported in 71 individuals. To explore possible genotype–phenotype correlations, the available clinical data were collected (Table S5; Balasubramanian et al, ; Capo‐Chichi et al, ; Kortum et al, ; Maksimova et al, ; Megarbane et al, ; Regateiro et al, ; Segarra et al, ; Staufner et al, ; E‐P03.292008: European Society of Human Genetics 2018 meeting). A total of 36 patients have been reported to carry the homozygous p.Arg1914His change associated with the SOPH phenotype (Maksimova et al, ; Park & Lee, ), while two patients were reported to have a skeletal phenotype associated with the homozygous c.6237−3C>G splice‐site change (Palagano et al, ; Prontera et al, ).…”
Section: Introductionmentioning
confidence: 99%